THE POLITICISATION OF LITHUANIAN EDUCATIONAL ORGANISATIONS MANAGEMENT: A COMPARATIVE ANALYSIS OF VILNIUS CITY AND VILNIUS DISTRICT MUNICIPALITIES - Čeponytė, Eglė (Politologija, 2014)
This research analyses the change and politicisation of educational management in Lithuania in 2001–2013, as well as the impact of reforming the educational managers’ recruitment procedures on the scope of politicisation. According to the data analysis, 39% of managers in Vilnius city and Vilnius district are politicised. The politicisation level is even higher (50%) among the managers who were selected through the new recruitment procedures. This is a concern because the level of politicisation in public educational organisations is higher than in other public sector organisations (government agencies or state-owned companies). Furthermore, contrary to the initial expectations, reforming the recruitment system has not decreased the politicisation level. The aim of this research is to identify factors that stimulate different behavioural strategies (‘top-down’ and the ‘bottom-up’ politicisation) and affect the actual level of politicisation. In order to achieve this aim, data were collected on the political engagement of 168 managers currently employed in public educational organisations in Vilnius city and Vilnius district as well as 64 managers who were appointed under the new recruitment procedures. Moreover, a survey of 58 public educational institutions was conducted in order to gather data on the career patterns (appointment and dismissal dates) and professional background of the former managers.